Ask questions and get helpful answers.
Ask a New Question

The equation 2sinx+sqrt(3)cotx=sinx is partially solved below.

2sinx+sqrt(3)cotx=sinx
sinx(2sinx+sqrt(3)cotx)=sinx(sinx)
2sin^2x+sqrt(3)cosx=sin^2x
sin^2x+sqrt(3)cosx=0

Which of the following steps could be included in the completed solution?
a. cos^2x-sqrt(3)cosx-1=0
b. sin^2x-sqrt(3)sinx-1=0
c. (1-cos^2x)(sqrt(3)cosx)=0
d. (1-sin^2x)(sqrt(3)sinx)=0

  1. 👍
  2. 👎
  3. 👁
  4. ℹ️
  5. 🚩

7 answers

  1. 1. A [ cos^2 (x) - sqrt(3)*cos(x) - 1 = 0 ]
    2. B [ f(x) = sqrt(sin x) ]
    3. D [ 7.6 hours ]
    100% ur welcome

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩
  2. No Steve is actually correct, A, or cos^2x - sqrt3 cos x - 1 = 0 is correct

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩
  3. looks like A to me
    Then everything is in terms of cosx

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩
  4. Tysm Yuh!

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩
  5. You're amazing @Yuh !!! Thank you so much<3 100%

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩
  6. Trigonometric Equations Practice:
    1. (A): cos^2 (x) - sqrt(3)*cos(x) - 1 = 0
    2. (B): f(x) = sqrt(sin x)
    3. (D): 7.6 hours
    Trigonometric Equations:
    1. (C): three
    2. (B): The equation was factored incorrectly.
    3. (A & E) sec x= -1 & sec x=3/2
    4. (B): sqrt2/2

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩
  7. ^^ 100% correct! :)

    1. 👍
    2. 👎
    3. ℹ️
    4. 🚩

Answer this Question

Related Questions

Still need help?

You can ask a new question or browse existing questions.